18F-FDG PET/CT SUVmax in pleuropulmonary solitary fibrous tumors: can it be incorporated into risk classification systems for predicting recurrence? - İlteriş Türk; Mehmet Çetin; Necati Solak; Ali Can Kayaaslan; Nesrin Gürçay; Ebru Tatcı; Göktürk Fındık; Pınar Bıçakçıoğlu; Selim Şakir Erkmen Gülhan (BMC Pulmonary Medicine)
Abstract Background Several studies have been conducted to identify the parameters associated with the aggressive course of pleuropulmonary solitary fibrous tumors (SFT) following surgical treatment, and various classification systems have been proposed for assessing risk. Methods The surgical outcomes of patients with pleuropulmonary SFT who underwent surgery between 2009 and 2024 at our center were retrospectively evaluated. Parameters of patients who experienced recurrence during follow-up were analyzed, and the risk classification systems proposed by Demicco were tested on our patient cohort. The pozitron emision tomography/ computed tomography (PET/CT) standart uptake value(SUVmax), which was significantly associated with recurrence, was incorporated into the modified Demicco classification, and a new classification model was developed and compared with existing models. Results Among the 79 included patients, 21.5% had intraparenchymal tumors, which were excised along with various parenchymal resections, while pleural tumors underwent mass excision. The postoperative follow-up period was 108.16 ± 44.09 months, during which 7.6% of patients experienced recurrence. Tumor size (p = 0.023), mitotic index (p < 0.001), presence of necrosis (p = 0.007), and PET/CT SUVmax value (p = 0.005) were found to be significantly associated with recurrence. The PET/CT SUVmax value, which was not included in Demicco’s classifications, ranged from 1.12 to 7.98, with a cutoff value of 4.50. The addition of SUVmax to the modified Demicco classification categorized all patients with recurrence into the high-risk group, and the new classification model strongly differentiated recurrence (p < 0.01, 100% sensitivity, 71.43% specificity). Conclusion The incorporation of SUVmax into the modified Demicco classification system for pleuropulmonary SFT provides a more significant prediction of recurrence.